2010
DOI: 10.1088/0022-3727/43/26/265201
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle synthesis using high-powered pulse-modulated induction thermal plasma

Abstract: Abstract. Nanoparticle synthesis was performed using high-powered pulsemodulated induction thermal plasma (PMITP) technique to study the effect of coil current modulation on synthesized nanoparticles. This is the first paper to present a summary of results of TiO 2 nanoparticle synthesis using high-power Ar-O 2 PMITP at 20 kW. The synthesized particles were analyzed using a field emission scanning electron microscope (FE-SEM), and X-ray diffractometry (XRD). In addition, optical emission spectroscopy (OES) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 41 publications
(71 reference statements)
3
28
0
Order By: Relevance
“…This enhancement of the time-averaged temperature gradient has been observed also in other applications of the PMITP in experiments and numerical simulations conducted in our previous works [15,20]. Actually, our previous study related to nanoparticle synthesis using PMITP [17], revealed that the higher degree of the coil current modulation for the PMITP can provide smaller TiO 2 nanoparticles at a fixed duty factor (DF) of 80%, and that the weight fraction of anatase-TiO 2 nanoparticles to the synthesized particles were 80-90%, almost irrespective of the modulation degree. In addition, our estimation of the time-averaged temperature in the reaction chamber revealed that the time-averaged temperature was decreased by the modulation of the coil current even at the same input power of 20 kW used in our previous study.…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…This enhancement of the time-averaged temperature gradient has been observed also in other applications of the PMITP in experiments and numerical simulations conducted in our previous works [15,20]. Actually, our previous study related to nanoparticle synthesis using PMITP [17], revealed that the higher degree of the coil current modulation for the PMITP can provide smaller TiO 2 nanoparticles at a fixed duty factor (DF) of 80%, and that the weight fraction of anatase-TiO 2 nanoparticles to the synthesized particles were 80-90%, almost irrespective of the modulation degree. In addition, our estimation of the time-averaged temperature in the reaction chamber revealed that the time-averaged temperature was decreased by the modulation of the coil current even at the same input power of 20 kW used in our previous study.…”
Section: Introductionsupporting
confidence: 73%
“…We have started studying nanoparticle synthesis using a modulated induction thermal plasma [17]. The two following main effects can be expected in nanoparticle syntheses using modulated thermal plasmas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The modulation cycle was fixed at 15 ms. The reason to select the modulation cycle of 15 ms is attributed to the fact that the residence time of the reactant vapour was estimated as 10-20 ms according to the gas flow velocity calculation by numerical thermo-fluid simulation [19]. It is expected for this time period to provide sufficient evaporation of the injected powders in the high-temperature region in the plasma during the on-time, and successive rapid cooling of the plasma tail during the off-time.…”
Section: Experimental Conditionsmentioning
confidence: 99%
“…The authors recently developed a new synthesis method of large amounts of pure oxide nanopowder without contamination using pulse-modulated induction thermal plasma (PMITP) with time-controlled feeding of feedstock (TCFF) [19]- [21]. The PMITP was developed by our group to control the temperature and chemical activity fields in thermal plasmas using coil-current modulation [23,24].…”
Section: Introductionmentioning
confidence: 99%